2010
DOI: 10.1068/a4291
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining the Influence of Work and Nonwork Accessibility on Residential Location Choices with a Microanalytic Framework

Abstract: IntroductionGenerally defined as the ease of access between entities in different locations (Harris, 2001), the concept of accessibility reflects the possibilities for activities, such as employment and shopping, and has long been theorized as a principal determinant of residential choice behavior. The classic monocentric city model in urban economics held central the trade-off relationship between commuting and land costs in explaining household locations (Alonso, 1964;Muth, 1969).Research on the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 36 publications
(55 reference statements)
3
40
0
2
Order By: Relevance
“…If dwelling is a choice alternative, it is possible to interact household attributes with residential units attributes, e.g., household size in relation to apartment size. Lee and Waddell (2010a) conclude that these dwelling characteristics tend to dominate accessibility indicators. Our own study in the Zurich area also showed that including dwelling characteristics strongly enhanced the models (Schirmer et al 2013).…”
Section: Residential Unitmentioning
confidence: 99%
See 4 more Smart Citations
“…If dwelling is a choice alternative, it is possible to interact household attributes with residential units attributes, e.g., household size in relation to apartment size. Lee and Waddell (2010a) conclude that these dwelling characteristics tend to dominate accessibility indicators. Our own study in the Zurich area also showed that including dwelling characteristics strongly enhanced the models (Schirmer et al 2013).…”
Section: Residential Unitmentioning
confidence: 99%
“…Zolfaghari et al (2012) see a positive price impact when constraining the choice set based on price, indicating that households choose the best available alternative within a certain range. Ratio of price to household income is also significant when it is the only price-related variable in the model specification (Belart 2011;Bürgle 2006;Lee and Waddell 2010a;Waddell 2006;Weisbrod et al 1980;Zhou and Kockelman 2008). Walker and Li (2007) observe that price sensitivity decreases with rising income; integration of the ratio and, ultimately, the logarithmic transformation seems reasonable.…”
Section: Costs Price and Valuementioning
confidence: 99%
See 3 more Smart Citations